The Feminist Museum Hack: Making a creative disruptive pedagogical, investigative and analytical tool (Revista Lusófona de Educação, 2019)
How do we illuminate patriarchal ideologies that hide in plain sight in museums and art galleries and still play a powerful active role shaping andmobilising problematic gendered constructions that re-enforce gender and oppression? This question was central to our development of the Feminist Museum Hack, an innovative pedagogical, investigative, analytical and interventionist practice we have designed to use in the complex context of cultural institutions. In this article, we share the various components of the Hack, its aim to strengthen analytical and visual skills and connect disconnects of language and image. The Hack makes a valuable contribution to feminist adult education by enabling us to see the unseen of intrinsic patriarchal ideologies in museums. Further, the Hack works to develop imagination and sharpen an oppositional feminist gaze, giving us a sense of agency with which to disrupt the privileged authority of museums and unearth their problematic discursive, visual and rhetorical politics that have implications for seeing and knowing gender beyond their walls.Keywords: museums; feminist cultural theory; agency; representation; authority; the unseen